The quest for justice: Martin Luther King, Jr.'s civil disobedience - Pattaro, Sanwapat (2013)
Martin Luther King, Jr. is widely known as a Black Gandhi who was lighting back to remedy segregation and racism in American social structure. The oppressed structure was cultivated more than 100 years; the time of colonialism to imperfect Democracy. King has highly expected how to remedy the social illness and pushed him to say a famous state "I have a dream".One days the river of justice will flow conveniently, after that the time of endurance over in case of Rosa Park, he became the leader of nonviolent campaigns for Civil Rights movement. Mass civil disobedience becomes a nonviolent weapon to remedy social illness to quest for justice for African-Americans.The study is philosophical investigation on King's Civil Disobedience.The main aim is to analyze the concept of King's civil disobedience and finds out some proposals to remedy political crisis in Thailand, Red and Yellow shirts.Perhaps the study will got some proposals from King's Perspective.His views mass civil disobedience is nonviolent direct action to disobeying illegitimate laws, commands and policies.His civil disobedience proposes that conscience needs to relate to the kingdom of Truth based on Christian philosophy.